PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP MINAT BELI ULANG DENGAN PERSEPSI NILAI SEBAGAI VARIABEL INTERVENING - Elok Faiqotul H; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
AbstractAbstract               The purpose of this study was to determine the effect of service quality and brand image on repurchasing interest with perceived value as an intervening variable. The population and sample in the study were GrabExpress users in Lowokwaru District with respondents as many as 100 people. Data collection by distributing questionnaires. Data analysis in this study used SPSS version 16. The sampling technique used purposive sampling method and the data testing techniques used in this study included validity test, reliability test, classic assumption test and path.                The results of this study state that service quality and brand image have a significant positive effect on perceived value, service quality and brand image have a significant effect on repurchase interest, perception of value not positive which cannot mediate service quality to repurchase interest while perceived value has positive effect towards repurchasing interest that can mediate brand image Keywords: Service Quality, Brand Image, Repurchase Interest, and Value Perception